ANALYZING THE DEVELOPMENT OF PHONOLOGYCALASPCETS IN SPEAKING CLASS TO STUDENTS OF ENGLISH AS A FOREIGN LANGUAGE (EFL) IN JENDERAL SOEDIRMAN UNIVERSITY - Rochman, Syaifur (Journal of English and Education (JEE), 2010)
The differences in phonological systems between Indonesian and English systems are the central problems that university students often encountered in speaking practice. Students usually transfer the system of their own mother tongue to the target language. This article is intended to explore the problems of EFL students in Jenderal Soedirman University in speaking the target language correctly. The discussion focused on the typical mistakes that the university students made in phonological aspects. Analysis was given to problems in the aspect which occurred during their speaking class. It was hoped that this could become an idea of the EFL teacher to devise the materials for teaching students in tertiary level.